ST Elevation Myocardial Infarction in Patients with COVID-19: Case Series - Sofia Lakhdar; Chandan Buttar; Laura Guzman Perez; Nso Nso; Mahmoud Nassar; Giovina Collura (European Medical Journal)
Severe acute respiratory syndrome coronavirus 2, or COVID-19, has triggered an unprecedented pandemic situation across the globe. Patients with COVID-19 frequently experience a range of clinical complications driven by their health status, comorbidities, and disease responsiveness. Patients with COVID-19 also encounter cardiovascular conditions that potentially increase their risk for mortality. Few clinical studies reveal the development of ST segment elevation myocardial infarction (STEMI) in patients with COVID-19. New York City, USA, continues to witness and report a high incidence and prevalence of COVID-19 infections. New York City’s healthcare centres and hospitals have treated more than 6,000 cases of COVID-19 pneumonia in their inpatient and intensive care units. The authors conducted a retrospective study of patients admitted to NYC Health + Hospitals, Queens, New York City, USA, with confirmed COVID-19 reverse transcriptase-PCR test findings between 29th March 2020 and 1st May 2020. The authors used a retrospective case series design to evaluate the association between laboratory-confirmed COVID-19 infection and hospitalisation for acute myocardial infarction. They utilised a series of ECGs to record and analyse STEMI patterns across patients with COVID-19. This study aimed to determine the risk/incidence of STEMI in patients with COVID-19, and its impact on their clinical presentation, angiographic findings, and clinical outcomes. The authors hypothesised STEMI as a significant COVID-19 complication, with the potential to impact the long-term prognostic outcomes of patients with COVID-19.